Antibacterial activity test of nipah leaf extract in inhibiting the growth of streptococcus sanguinis ATCC 10556 on the surface of heat-polymerized acrylic resin: Study experimental - Ferdina, Resa; Ardila, Vidia Ananda; Lestari, Citra; Sari, Widya Puspita (Padjadjaran Journal of Dental Researchers and Students, 2026)
ABSTRACT Introduction: Heat-polymerized acrylic resin denture bases are susceptible to increased Streptococcus sanguinis counts, which can lead to oral health problems. Sodium hypochlorite, commonly used as a denture cleanser, has the potential to damage the physical properties of acrylic resin. Therefore, natural alternatives are needed as a substitute for denture cleaners such as nipah leaf extract (Nypa fruticans wurmb) which has antibacterial bioactive compounds. This study analyzes the antibacterial activity of nipa palm leaf extract in inhibiting the growth of Streptococcus sanguinis ATCC 10556 on the surface of heat-polymerized acrylic resin. Methods: The study used a laboratory experiment, with a post-test only control group design where acrylic resin plates measuring 10 × 10 × 1 mm, which were divided into five treatment groups inoculated with Streptococcus sanguinis were treated with nipah leaf extract with concentrations of 10%, 15%, 20%, and a control group. Then, bacterial growth was calculated and analyzed using the Least Significant Difference test with a sig value p<0.05. Results: Nipah leaf extract has been proven to inhibit the growth of Streptococcus sanguinis. A concentration of 10% showed a lower colony count compared to concentrations of 15% and 20%, so under the conditions of this study, a concentration of 10% showed a tendency to provide a better inhibitory effect. Conclusion: Nipah leaf extract inhibits the growth of Streptococcus sanguinis on acrylic resin surfaces. A concentration of 10% showed better inhibitory effect.KEYWORDS: antibacterial activity, nipah leaf extract (Nypa Fruticans Wurmb), Streptococcus sanguinis, heat-cured acrylic resin.Uji aktivitas antibakteri ekstrak daun nipah dalam menghambat pertumbuhan streptococcus sanguinis ATCC 10556 pada permukaan resin akrilik polimerisasi panas: Studi eksperimentalABSTRAK Pendahuluan:  Basis gigi tiruan dari resin akrilik polimerisasi panas rentan terhadap peningkatan jumlah Streptococcus sanguinis, yang dapat menimbulkan masalah kesehatan mulut. Sodium hipoklorit, yang umumnya digunakan sebagai pembersih gigi tiruan, berpotensi merusak sifat fisik resin akrilik. Diperlukan alternatif alami sebagai pengganti pembersih gigi tiruan seperti ekstrak daun nipah (Nypa fruticans wurmb) yang memiliki senyawa bioaktif antibakteri. Penelitian ini menganalisis aktivitas antibakteri ekstrak daun nipah dalam menghambat pertumbuhan Streptococcus sanguinis ATCC 10556 pada permukaan resin akrilik polimerisasi panas. Metode: Penelitian menggunakan eksperimental laboratorium, dengan post test only control group design dimana plat resin akrilik berukuran 10 × 10 × 1 mm yang dibagi menjadi lima kelompok perlakuan yang diinokulasi Streptococcus sanguinis diberi perlakuan ekstrak daun nipah dengan konsentrasi 10%, 15%, 20%, dan kelompok kontrol. Selanjutnya pertumbuhan bakteri dihitung dan dianalisis menggunakan uji Least Significant Different dengan nilai p<0,05. Hasil: Ekstrak daun nipah menurunkan pertumbuhan Streptococcus sanguinis. Konsentrasi 10% menghasilkan jumlah koloni lebih rendah daripada 15% dan 20%, menunjukkan efek penghambatan yang lebih baik pada kondisi penelitian ini. Simpulan: Ekstrak daun nipah menghambat pertumbuhan Streptococcus sanguinis pada permukaan resin akrilik. Konsentrasi 10% memberikan daya hambat terbaik.KATA KUNCI: aktivitas antibakteri, ekstrak daun nipah, Streptococcus sanguinis, resin akrilik polimerisasi panas.